(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Cleaning products play an essential role in daily life. They can remove dirt and stains from our clothes. Lemon is a natural choice when removing fabric stains, making it an excellent alternative to harsh bleaches and other chemicals. Unsightly stains are no match for the power of lemons to clean. Creating an Investigative Project on Lemon (Citrus limon) soap as an effective stain removal will greatly help teachers and students because it will lessen their budget for laundry. The research design used for the study was the non-probability purposive sampling technique. The statistical treatment used for this study was a t-test to determine the difference between the two groups of respondents. The instrument utilized in this study was a survey questionnaire; the researchers surveyed to identify the level of acceptability of the Lemon Soap in terms of ingredients, procedural methodology, effectivity, and presentation. The respondents of the study are composed of 12 Grade 12 STEM students and 4 Grade 12 STEM teachers. The following procedures were undertaken in the process of developing and making the Lemon Soap: First, prepare all materials needed for this project, slice the five lemons into four parts (remove the seeds of the lemon) and then squeeze, slice the glycerin, put it into the blender, we need to melt the glycerin soap in the casserole, after melting the glycerin soap we need to put the blended lemon in the casserole, 20 ml of vinegar, and two tablespoons of baking soda, keep stirring until it boils, after that, we need to place it into the moulder and leave it for at least one hr., finalize the package of the product. The study results regarding Ingredients, procedural methodology, effectivity, and presentation are acceptable as assessed by the Grade 12-Stem Teachers and Grade 12-Stem Students. Table 12 presents the significant difference between the assessments of the two groups of respondents. The acquired overall mean of the Grade 12 STEM teachers is 4.29 with a variance of 0.077011, a t-computed mean of 12.90035 and a degree of freedom of 41 with a value of 2.0196 the t-computed > t-critical. Therefore, the assessment of the Grade 12 STEM students is accepted. The acquired overall mean of the Grade 12 STEM students was 3.40 with a variance of 0.035941 a t-computed 12.90035 a degree of freedom of with a value of 2.0196 the t-computed > t-critical. Therefore, the assessment of the Grade 12 STEM teachers is accepted. There is no significant difference between the assessments of the groups of the groups of respondents as a forecited variable.